THE EFFECT OF USING SWELL METHOD ON STUDENTS’ ACHIEVEMENT IN WRITING PROCEDURE TEXT - Ayu Wulandari and Rahmad Husein (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2014)
This study aims at investigating the effect of using SWELL Method on Students’ Achievement in Writing Procedure Text. This study was conducted by experimental research. The population of this study was the students of the third grade of SMP NEGERI 2 SELESAI. The total number of the population was one hundred twenty in 4 classes. There were sixty students chosen as the sample using randomly by lottery technique. The sample was divided into two groups, namely experimental group and control group. The experimental group was taught by using SWELL Method and control group was taught by using Demonstration Method. The instrument for collecting the data was writing test. The data was analyzed by using t-test formula. The result of the analysis shows that t-observed value is higher than t-table (2.26>2.00) at level of significance 0.05 with the degree of freedom 58. It means that the alternative hypothesis (Ha) is accepted and null hypothesis (Ho) is rejected. Based on the findings of this study, it was found that there is a significant effect of SWELL Method on students’ achievement in writing procedure text.